THE ROLE OF LAW IN PROTECTING THE RIGHTS OF PERSONS WITH DISABILITIES - Qamariyanti, Yulia; Al-Ghifari, Muhammad Farhan; Farghana, Nur Muhammad Zulyan Farghana; Kasehung, Gloria Stefanna; Irfan, Muhammad; Jannati, Fia; Al Farizi, Muhammad Refi; Zaidir, Firman Dzakir (CV. Strata Persada Academia, 2024)
Every individual has equal human rights, without discrimination based on physical differences, skin color, race, ethnicity, or beliefs. This also applies to persons with disabilities who have the right to equal treatment. However, persons with disabilities often face discrimination, especially in obtaining employment. Law Number 8 of 2016 on Persons with Disabilities provides legal guarantees for persons with disabilities to obtain protection and fulfillment of their rights. Nevertheless, the implementation of these rights is still not optimal. This study uses a normative method with a statutory approach to analyze the legal protection for persons with disabilities from violence, exploitation, and in terms of employment. The results show that although there is a strong legal basis, its implementation still faces various challenges, such as social stigma, weak law enforcement, and lack of accessibility. Therefore, further efforts are needed to overcome these obstacles to effectively realize legal protection for persons with disabilities.